Current status and future prospects of grapevine anthracnose caused by Elsinoe ampelina: An important disease in humid grape‐growing regions. (7th June 2021) - Li, Zhi; dos Santos, Ricardo Feliciano; Gao, Linlin; Chang, Pingping; Wang, Xiping
Abstract: Anthracnose, caused by Elsinoe ampelina, is one of the most destructive diseases of grapevines worldwide, especially in humid areas. E . ampelina mainly infects young tissues starting from shoots to berries and affects vine vigour and berry yield. The occurrence and the role of the sexual stage in the disease cycle and the grapevine– E . ampelina interaction remain poorly understood. However, the recent genome sequence data of E . ampelina provides the basis for further studies to understand its evolution, pathogenicity mechanisms, and effector repertoire. New studies on E . ampelina have been conducted in recent years. In this pathogen profile, we present a comprehensive literature review of E . ampelina to summarize the findings on its aetiology, infection mechanisms, genome, pathogenicity, and host resistance. Taxonomy: Elsinoe ampelina Shear; Kingdom Fungi; Phylum Ascomycota; Subphylum Pezizomycotina; Class Dothideomycetes; Subclass Dothideomycetidae; Order Myriangiales Starbäck; Family Elsinoaceae Höhnel; Genus Elsinoe Racib. Host range: E . ampelina only infects Vitis species and hybrids. Distribution: The grapevine anthracnose is distributed worldwide but is most prevalent in Argentina, Australia, Brazil, Canada, China, India, Japan, Korea, New Zealand, South Africa, Thailand, USA, and Uruguay. Disease symptoms: E . ampelina causes slightly abundant depressed spots on young leaves, petioles, stems, tendrils, rachises, and berries. Under severe infection conditions, early defoliation, berry dropping, and delayed berry development and ripening may occur. Genome: The genomes of two E . ampelina isolates, YL‐1 and CECT 20119, are publicly released with 8, 057 and 10, 207 predicted genes, respectively. Abstract : This pathogen profile presents a comprehensive literature review of grape anthracnose, caused by Elsinoe ampelina, to summarize the findings on the life cycle and provide current knowledge on what we know about this disease so far.